Critical Aspects of Endometrial Polyp Clinical Management: A Narrative Review - Oronzo Ruggiero Ceci; Mario Franchini (Clinical and Experimental Obstetrics & Gynecology)
Objective: Endometrial polyps are one of the most often diagnosed gynecological pathologic findings, affecting women from reproductive age to advanced menopause. In women of childbearing age, they can cause infertility, although a clear cause-and-effect relationship is not always evident. In postmenopausal women, endometrial polyps may manifest primarily with abnormal uterine bleeding (AUB). They are usually benign lesions, and the malignant transformation, especially in menopausal women, occurs infrequently increasing with age. The ultrasound suspicion of an endometrial polyp requires a better definition of its size, position, and nature through hysteroscopy. Hysteroscopy performed as an outpatient procedure, in addition to diagnosis may be followed by the simultaneous removal of the polyp (see & treat approach). If this is not possible in an outpatient setting, polypectomy can be performed in the operating theatre by means of resectoscopy or mechanical hysteroscopic tissue removal (mHTR) system. This critical study about the management of endometrial polyps, intends to examine what is still being discussed in this regard. Mechanism: A narrative review was conducted analyzing the available literature regarding the management of endometrial polyps in infertile childbearing age and pre and postmenopausal women. Findings in Brief: There is no agreement that all endometrial polyps should be removed. Polyps <10 mm can be monitored over time. In infertile women, polypectomy is recommended because it is a possible impediment to fertilization, or for Assisted Reproductive Technology (ART) procedures, however not all studies are of agreement. For patients with polyps symptomatic of AUB, polypectomy must always be recommended. Conclusions: Following an endometrial polyp diagnosis by hysteroscopy, the decision to operate should be considered for infertile women or for those with large or symptomatic menopausal polyps. Due to the lack of clear guidelines, the decision can be postponed by adopting careful surveillance in some cases.